ISLAMISASI NUSANTARA (Analisis Terhadap Discursus Para Sejarawan) - Husaini Husda (Jurnal Adabiya, 2016)
Indonesia is the largest country in the world community with more than 200 million Muslims. However, when Islam arrived, where the first Muslim set foot in this area, and who was the bearer of Islam to Indonesia, are still big question that historians continue to debate whichraise a not ending discussion that ends with the birth of the various theories about the process of arrival of Islam in Indonesia. At least, there are four theories emerged by historians by bringing forwatd a variety of sources and interpretation of diverse arguments. Those theories are the theory of India, the theory of Arabic, the theory of Persian and later the theory of China.